A non‐coding RNASEH1 gene variant associates with type 1 diabetes and interacts with HLA tagSNPs in families from Colombia. Issue 7 (23rd July 2020) - Gomez‐Lopera, Natalia; Alfaro, Juan‐Manuel; Rodriguez, Alejandra‐Marcela; Ramirez, Alex; Leal, Suzanne M.; Pineda‐Trujillo, Nicolas
Abstract: Objectives: RNASEH1 gene has recently been associated with type 1 diabetes (T1D) in Colombia. The purpose of this study was to fine mapping the putative functional variant in RNASEH1 and testing its interaction with HLA tagSNPs. Methods: Two‐hundred nuclear families with T1D were included in this study. Probands were tested for GAD65 and IA‐2 autoantibodies. Genotyping was performed using 20 coding tagSNPs uncovered through Sanger sequencing (N = 96), in addition to 23 tagSNPs chosen from 1000genomes to cover the extent of the gene region. Also, 45 tagSNPs for classic HLA alleles associated with T1D were also genotyped. The transmission disequilibrium test (TDT) was used to test for association and a multiple testing correction was made using permutation. Interaction between RNASEH1 variants and HLA was evaluated by means of the M‐TDT test. Results: We identified 20 variants (15 were novel) in the 96 patients sequenced. None of these variants were in linkage disequilibrium. In total, 43 RNASEH1 variants were genotyped in the 200 families. Association between T1D and rs7607888 was identified ( P = .002). Haplotype analysis involving rs7607888 variant revealed even stronger association with T1D (most significative P = .0003). HLA tagSNPs displayed stronger associations (OR = 6.39, 95% CI = 4.33‐9.44, P ‐value = 9.74E‐28). Finally, we found several statistically significant interactions of HLA variants with rs7607888 ( P ‐value ranged from 8.77E‐04 to 5.33E‐12). Conclusion: Our results verify the association of rs7607888 in RNASEH1 gene with T1D. It is also shown in the interaction between RNASEH1 and HLA for conveying risk to T1D in Northwest Colombia. Work is underway aiming to identify the actual classic HLA alleles associated with the tagSNPs tested here.